Violation Of Human Rights - The Woes Of Minority Community In Rohinton Mistry’s Such A Long Journey (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper showcases the problems faced by the minority community – The Parsis living in a secular country, India. Rohinton Mistry depicts the woes and worries, burdens and troubles experienced by this minority community owing to corruption. When corruption rules, basic human rights and liberties come under threat as corruption affects civil, political, economic, social and cultural rights of a person. The protagonist Gustad’s long journey in a cold and malevolent world in which all forms of happiness and misery are inseparably woven is the journey of an ethnic group on the verge of extinction still fighting for their rights.